An estimation method of wind energy curtailment considering wind generator tripping in frequency adjustment level. (15th October 2015) - Tian, Shuxin; Cheng, Haozhong; Zeng, Pingliang; Ma, Zhoujun; Liu, Lu
Summary: Development of wind farms clustering exerts significant influence on secure operation of power grid and also puts forward new requirements for the capacity of peak regulation and frequency adjustment. When power grid frequency is higher than 50.2 Hz, active power output of wind farm should be reduced gradually according to the command from control center of power grid. To study urgent wind power curtailment in frequency adjustment level, math formula of frequency adjusted sensitivity index is deduced, which determines wind generator tripping strategy if the lopsided active power has occurred. Typical frequency adjustment time intervals are selected according to the relationship between frequency overshoot time and load variation as wind power gets curtailed. The annual wind energy curtailment in frequency adjustment level is estimated by selecting the most appropriate wind generator tripping and comparable with wind energy curtailment in peak‐load regulation level on the basis of unit commitment model. Based on DIgSILENT/PowerFactory software, the effectiveness and feasibility of the proposed method are verified by taking China's a certain regional power network planning of 2020 as computational examples. Copyright © 2015 John Wiley & Sons, Ltd.